“Anyway, I don't think I’ll ever be prepared”: Letters students’ beliefs and affective states - de Lima, Fernando Silvério; Candido Ribeiro, Douglas; Pereira Zolnier, Maria da Conceição Aparecida (Revista Letras, 2013)
Some studies in contemporary Applied Linguistics have considered the role of beliefs and affective domains in initial and continuing English Teacher Education. In this paper we present the results of a case study (BROWN; RODGERS, 2002), carried out with two Letters undergraduates, in which we aimed to investigate the beliefs and affective states that emerged in the classes of an English course in which the students were enrolled. The data, collected mainly by means of written accounts which resulted from open questionnaires, suggest a consistent relationship between beliefs and affective states, i. e., the students do not feel prepared for the teaching profession, pointing out some limitations that are justified by their beliefs and strengthened by factors of the affective domains, such as insecurity and anxiety.